2012
DOI: 10.5606/tjr.2012.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Recommendations for the Management of Knee Osteoarthritis: A Consensus Report of the Turkish League Against Rheumatism

Abstract: Amaç: Diz osteoartriti (OA) sık görülen ve neden olduğu ağrı ve sakatlık sonucunda sosyoekonomik yük bindiren bir hastalıktır. Türkiye Romatizma Araştırma ve Savaş Derneği (TRASD) OA tedavisi ile uğraşan hekimlere günlük klinik uygulamalarında yardımcı olmak amacıyla, uzman görüşleri ile desteklenmiş, ulusal "diz osteoartrit tedavisinde kanıta dayalı önerileri" hazırlamak için bir proje başlatmıştır. Objectives: Knee osteoarthritis (OA) is a common disease which causes pain, disability and great socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 72 publications
0
29
0
9
Order By: Relevance
“…Acetaminophen is suggested as the first option in many OA treatment guides. In cases where paracetamol is ineffective for symptomatic knee OA, NSAII use is listed in almost all suggestions or guides [17]. As the primary complaint by most of the patients with OA is pain, ratio of the patients using NSAII and paracetamol, which are frequently used for pain, was identified to be 86% and 66%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen is suggested as the first option in many OA treatment guides. In cases where paracetamol is ineffective for symptomatic knee OA, NSAII use is listed in almost all suggestions or guides [17]. As the primary complaint by most of the patients with OA is pain, ratio of the patients using NSAII and paracetamol, which are frequently used for pain, was identified to be 86% and 66%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in various treatment guides developed in accordance with evidence‐based procedures that superficial local hot applications may have beneficial effects on pain and functional status in selected patients without active synovitis while superficial local cold application may be recommended in the presence of synovitis. It is also stated that hot and cold applications can decrease the pain in knee osteoarthritis and improve physical function (Tuncer et al., ; Zhang et al., ). Brosseau et al.…”
Section: Introductionmentioning
confidence: 99%
“…status in selected patients without active synovitis while superficial local cold application may be recommended in the presence of synovitis. It is also stated that hot and cold applications can decrease the pain in knee osteoarthritis and improve physical function (Tuncer et al, 2012;Zhang et al, 2008). Brosseau et al (2003) reported in their review that cold applications provide significant benefits regarding the range of motion in the knee joint and the function and muscle strength in individuals with knee osteoarthritis, but has no significant effect on the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Last year, the Turkish League Against Rheumatism (TLAR) provided recommendations for the management of osteoarthritis (OA), RA, and ankylosing spondylitis (AS) by taking into consideration the health care system of our country. [6][7][8] These recommendations emphasized the importance of non-pharmacological interventions. The rehabilitative treatment approach included educational programs (lifestyle alterations, weight control, joint protection, and energy consumption), physical therapy modalities [thermotherapy, cryotherapy, electrotherapy, transcutaneous electrical nerve stimulation (TENS), and laser therapy], exercise (range of motion, strengthening, stretching, flexibility, muscle conditioning, aerobics, and cardiopulmonary fitness), ergonomic arrangements, assistive and adaptive devices, protective and corrective orthoses, appropriate footwear, and hydrotherapy (balneotherapy, spa, and aquatherapy).…”
mentioning
confidence: 99%